Mayer’s Model of Solving Routine and Non-Routine Problems in Linear Word Problems - Azobit Charles Awindago; Clement Ayarebilla Ali (Scientia Publica Media, 2026)
The Mayer model posits that students learn better from words and pictures than from words alone [HPX1.1], since dual representation of knowledge helps learners to construct verbal and pictorial mental models together and build connections between them. This study adopted Mayer’s (1985) model, consisting of problem translation, problem integration, solution planning, and solution execution, to examine problem-solving tasks. The objectives of the study were to translate, integrate, plan, and execute the four phases of linear word problems [HPX2.1]. The methods deployed a convergent parallel design to collect quantitative and qualitative data to compare and interpret the findings. The population was 638 students, comprising 400 and 238 from schools A’ and B’, and the sample was 350 students, comprising 200 and 150, respectively. And the ages ranged from 15 to 19 years [HPX3.1]. The data were collected through questionnaires and interview guides to complement and enhance validity and reliability. The data was analyzed through descriptive statistics and documents. The respondents had ethical consent, anonymity, permission, and voluntary participation. The key findings showed that the translation phase showed a significant negative statement, but a high presence of undecided responses across both non-routine linear word problems. Integration showed higher performance of students at higher percentiles, even though there were pronounced disparities between routine and non-routine linear problems, with routine problems showcasing higher average scores and less variability compared to non-routine problems. The planning phase showed differences in solving non-routine linear problems in expansion errors, clearing fractions, opening brackets, and grouping like terms. The execution phase consistently showed high percentages of errors in variable definitions and distribution. To minimize errors, we concluded that targeted interventions should strengthen and promote multidisciplinary, transdisciplinary, and interdisciplinary approaches to allow learners to translate, integrate, plan, and execute the four phases of linear word problems.